A new protein evaluation system for horse feed from literature data*. (4th February 2015) - Zeyner, Annette; Kirchhof, Susanne; Susenbeth, A.; Südekum, K.-H.; Kienzle, Ellen
Abstract: Few data on apparent pre-caecal digestibility (APCD) of crude protein (CP) and particularly amino acids (AA) are available from studies with horses. Protein bound in cell walls (i.e. neutral detergent insoluble CP (NDICP)) is unlikely to be decomposed by digestive enzymes in the small intestine. In contrast the corresponding analytical fraction of neutral detergent soluble CP (NDSCP) (NDSCP = CP−NDICP) is likely to be available for auto-enzymatic digestion. A literature analysis on the relationship between NDICP/NDSCP and pre-caecal indigestible/digestible CP was carried out. There was a strong positive relationship between NDICP and pre-caecal indigestible CP, which suggests that NDICP can be used to estimate the part of protein that is not available for digestion in the small intestine. There was also a correlation between NDSCP and pre-caecal digestible protein. The slope of the linear regression line between NDICP and pre-caecal digestible CP was 0·9, suggesting an APCD of NDSCP of 90 %. Thus pre-caecal digestible CP may be predicted by multiplying NDSCP by 0·9. Because the literature identifies a similar AA profile in NDICP and NDSCP within a given feed the presented concept may preliminarily be transferred to AA. The proposed system can at any time be adapted to the scientific progress without altering its structure. Such adaptations would be necessary particularly when new knowledge exist on the distribution of AA onto NDICP/NDSCP, the APCD of individual AA from NDSCP, and the impact of feed processing and chewing on particle sizes and protein digestibility.